Transnational Friendships and Fluid Boundaries in Early Childhood Classrooms: The Possibilities of (Un)Productive Play in Teacher–Researcher Collaborations for Equity. (July 2020) - Yoon, Haeny S.; Llerena, Carmen Lugo
Drawing from transnational feminism, we describe the interplay of multiple identities influencing teaching and research. By exploring our stories of border crossing as first/second-generation immigrant women, we highlight the importance of building communities of care in collaborative relationships. We explore the reciprocal relationship between play and work, creating the necessary conditions for democratic and dialogic partnerships. We aim to destabilize hierarchies between teachers/teacher educators toward more equitable, vulnerable, and flexible spaces of mutual accountability. Thus, we encourage fluid, boundary-crossing where personal relationships and professional work are not seen as binaries but interconnected and vital to critical work.